Synthesis and characterization of TiO2 nanoparticle films coated with organic dyes - Rika; Rahman M.Y.A.; Salleh M.M.; Umar A.A.; Ahmad A. (2023)
The synthesis and characterization of TiO2 nanoparticle coated with organic dyes, coumarin and methyl orange was reported. The films were deposited onto ITO-covered glass substrate by controlled hydrolysis technique asssited with spin coating technique. The films were characterized by scanning electron microscope (SEM), X-ray dispersive (XRD) technique and ultraviolet-visible (UV-Vis) spectrophotometer. The average grain size of the TiO2 films is about 76 nm. The uncoated TiO2 film is crystalline with anatase and rutile structure. The coated TiO2 films with dye are also crystalline since the diffraction peaks have been observed at three angles. The maximum absorption of the film coated with coumarine dye is at 480 nm. 2009 Elsevier B.V. All rights reserved.